Ultrastructural detection of lipids in the cephalic salivary glands of Apis mellifera and Scaptotrigona postica (Hymenoptera: Apidae) workers - Poiani, Silvana Beani [UNESP]; Cruz-Landim, Carminda da [UNESP] (Soc Brasileira Zoologia, Univ Federal Parana, 2016)
Secretory cells of the cephalic salivary glands (CSGs) of eusocial bees produce and accumulate lipid-like secretion in the lumens of their alveoli. Correspondingly, secretory cells present typical ultrastructural features of lipid-compound producers. Previous work on bees has revealed inter-specific differences in the chemical composition of secretion, and the production mechanisms and secretory cycle of secretory cells. In this work a comparative analysis of the mechanisms of lipid storage in the CSGs of Apis mellifera (Linnaeus, 1758) and Scaptotrigona postica (Latreille, 1807) workers was carried out. The ultrastructural location of lipids was ascertained using imidazole-osmium (IO), using individuals in different stages of their life cycles. Lipid deposits were identified inside glandular cells and in the alveolar lumens in all individuals, but differences were observed between the species. The glandular cells of A. mellifera workers presented positive reactions to IO as droplets dispersed in the cytoplasm, as vesicles and in the channels formed by apical plasma membrane infolds. In S. postica, lipid compounds were detected inside the mitochondrial matrix and in smooth endoplasmic reticulum cisterns. In both species, forager workers exhibited the largest amounts of lipids stored in the alveolar lumen. The differences between the species are discussed, taking into account specific behavioral differences.
Keywords: Cytochemistry; excretory; imidazole-osmium; insect; salivary system